Niedowierzanie i szok czy zdrowy rozsądek, czyli rekcja światowych mediów na wyniki brytyjskiego Brexitu - Smaga, Daniel (Political Preferences, 2017)
Disbelief and shock or common sense, the reaction of the world's media on the results of the British Brexit This article presents a new phenomenon, as yet unknown in the European Union. Namely to leave the country with Community structures. The first has made the United Kingdom, carried out by 23 June 2016. referendum. Slightly more than half the population of the British opted for the order to leave the European Union. Media the day after the announcement of the results Brexit began to comment on them. Not only in the UK but around the world could read in the newspapers that no one had expected. For many, it was shock and disbelief. I wonder what will be next? As further European Union will function without this power? What consequences await the British starting from the structures of the European Union? Will we see a domino effect in which other countries will leave the Community? Key words: Brexit, the European Union, media, referendum